The language of dissent – how school leaders adjust to policy change - Andre Kurowski (Educational Role of Language Journal, 2020)
Education has changed recently in the England and leadership of schools has changed with it. This paper examines the language of dissent, the political opposition of school leaders who meet the challenges of the educational system resulting from the government policies. They question whether these policies really serve the pupils and the community effectively. It is based on a wider piece of research involving interviews with head teachers and senior managers in a range of schools; it illustrates their frustrations at delivering a prescriptive curriculum. The research takes a grounded theory approach; throughout the interview process, themes emerged and were developed through layers of analysis. This led to the construction of a framework based on the ideas of power, ethics, resistance, and mistrust. This explains the views of school leader in conceptual terms, and it was found that they use of any form of control at their disposal, bring their own values to education, subvert where they see necessary, and at best tolerate policy.